Sesquiterpenes from the soil-derived fungus Trichoderma citrinoviride PSU-SPSF346 - Yaosanit, Wiriya; Rukachaisirikul, Vatcharin; Phongpaichit, Souwalak; Preedanon, Sita; Sakayaroj, Jariya (Beilstein Journal of Organic Chemistry, 2022)
Two new sesquiterpenes, trichocitrinovirenes A (1) and B (2), and five known compounds including four structurally related sesquiterpenes and one γ-lactone were isolated from the soil-derived fungus Trichoderma citrinoviride PSU-SPSF346. The structures were identified by analysis of their spectroscopic data. The relative configuration was assigned based on NOEDIFF data. The absolute configuration of compound 1 was established according to specific rotations and ECD data while that of compound 2 was proposed based on biosynthetic considerations. Compound 2 possesses a rare bicyclic sesquiterpene skeleton. The antimicrobial and cytotoxic activities of the isolated compounds were evaluated.
Keywords: antimicrobial activity; cytotoxic activity; γ-lactone; soil-derived fungus; sesquiterpene; Trichoderma citrinoviride